Relationship of Teachers’ Conceptual Knowledge of Biology with Students’ Achievement at Secondary Leve - Tallat Umbrin (JSE, 2023)
The research investigated the relationship of teachers’ conceptual knowledge of Biology with students’ achievement. The study was aimed at finding out the status of conceptual knowledge of teachers, its influence on students’ achievement, and its relationship with students’ achievement. The quantitative approach was used, or this research and a co-relational method was used to find relationships